Проблемы и перспективы развития налоговой системы Индии: индустриальный контекст - Гончаренко, Л.И.; Гурнак, А.В. (Економіка промисловості, 2016)
Рассматривается развитие индийской налоговой системы с момента провозглашения независимости государства и до сегодняшнего дня. В центре исследования вопрос о том, каким образом изменения и развитие налогового регулирования и налоговой политики повлияли на высокие темпы экономического роста Индии. Индийский опыт показал, что либерализация налогов в комплексе с другими мерами по реформированию экономики способствуют экономическому росту, если они нацелены не только на общее улучшение институциональной среды, но и на ускоренное развитие материального производства промышленности. В то же время существующие недостатки налоговой системы не являются критическим препятствием для экономического роста в текущем периоде, если налоги направлены на развитие и в целом соответствуют местным традициям государственности. Розглянуто розвиток індійської податкової системи з моменту проголошення незалежності держави і до сьогоднішнього дня. У центрі дослідження питання про те, яким чином зміни та розвиток податкового регулювання і податкової політики вплинули на високі темпи економічного зростання Індії. Індійський досвід показав, що лібералізація податків у комплексі з іншими заходами щодо реформування економіки сприяють економічному зростанню, якщо вони націлені не тільки на загальне поліпшення інституційного середовища, але і на прискорений розвиток матеріального виробництва, промисловості. У той же час існуючі недоліки податкової системи не є критичним обмеженням для економічного зростання в поточному періоді, якщо податки спрямовані на розвиток і в цілому відповідають місцевим традиціям державності. The paper studies the development of the Indian tax system since India became independent nation. We focus on how changes and developments in tax regulations and policies affect rapid economic growth in the country. Our focus is on direct and indirect taxes on industries in India and also on most important institutional tax problems. The key findings are as follows. Firstly, the Indian experience has shown that the tax liberalization in combination with other economic measures promote economic growth if focused not just on the general improvement of the institutional environment, but also on the accelerated development of material production industry. At the same time the existing shortcomings of the tax system is not a critical constraint to economic growth in the current period if, in principle, taxes are aimed at the development and broadly in line with local traditions of statehood. Secondly, the level of tax revenues in India nowadays is clearly inadequate to finance the state needs. At the same time, limiting its financial needs, the state contributes to the financial resources of economic entities. It is unlikely that India could surprise the world with such a high rate of economic growth if it had not happened the rethinking of the role of the tax system and its reform in order to create more favourable conditions for business. Thirdly, the implementation of tax solutions, which are considered as very effective from the perspective of the western theory and practice, has been faced with a lots of difficulties in specific institutional conditions of India. This fact is a strong confirmation that tax authorities cannot ignore or underestimate the influence of institutional and political factors on tax reform results. In many cases it turns out to be much stronger than the theoretical arguments and positive experience of other countries. And fourthly, the existing high tax rates do not reflect the actual tax burden. In the context of the formed institutional norms Indian business has developed and successfully applies its national recipe of tax burden optimization: through lobbying and using corruption schemes it achieves various tax preferences, as well as contributes to the preservation of the existing loopholes in the tax laws, and then legally avoids paying taxes.